Family‐related demands, positive orientation, coping strategies and family satisfaction: A mediation model - Suta, Joana M. (INYI Journal, 2015)
This study investigates how gradual social change may affect subjective well‐being (SWB) in the family domain, for example how it impacts family satisfaction. Individuals are active agents who use personal resources and coping strategies to protect their SWB from the effects of social change. Specifically, we predict that family demands affect SWB negatively, whereas positive orientation and coping strategies have a protective role. In a sample of 261 young Italian adults, family‐demands associated with social changes were found to have negative effects that could only be reduced from having a positive orientation. Furthermore, confirming the motivational theory of lifespan development, problem‐focused strategies were beneficial for family satisfaction to the extent that they represent an adaptation response to demands associated with social changes.